Students’ perception on exercising ethical influence towards organizational commitment / Nurull Fazlianna Awalludin - Awalludin, Nurull Fazlianna (Faculty of Business and Management, 2018)
The research was carried out to identify the impact of students’ perception on ethical influence towards organizational commitment. Although research have provided evidence that characteristics of the ethical influence effect the organizational commitment, these research were limited to the scope of characteristics the researcher examined. This research considered the effects of five elements of the ethical influence (reward power, coercive power, legitimate power, referent power and expert power) upon student perceptions towards organizational commitment. A set of questionnaire was adopted from past research to collect the primary data from the respondents about the relationship of ethical influence towards organizational commitment. The overall findings of the research indicates that based on the result, only reward power and legitimate power effect the organizational commitment, meanwhile coercive power, referent power and expert power do not effected the organizational commitment. As a conclusion, some suggestions have been made to improve the organizational commitment and recommendation for future studies has been included in the final part of the research.